Otomatisasi Kendali Power Window Berbasis Perubahan Konsentrasi Kadar Oksigen Dan Karbon Mono-Oksida Di Dalam Ruang Mobil - Achmad Komarudin; Fathoni Fathoni; Siswoko Siswoko (UIN Sunan Kalijaga Yogyakarta, 2020)
In the car, when we drive, we often know that a driver smokes in the car, the cigarette will produce smoke that is detrimental to the health of those who inhale it. Such as carbon monoxide gas that is inhaled will cause health problems until poisoning to result in death. Lack of oxygen levels in the body for the gas inhaler also results in drowsiness and can lead to accidents.To minimize this, the car must be equipped with a carbon monoxide sensor and an oxygen level sensor connected to the power window. So that the power window can open automatically according to the speed of the drive, i.e. when the sensor detects the target when the car is not driving (0km / h), the window will open 100% (40cm), when the car is driving at 1-40km / h, the car window will open by 75% (30cm), and when the car is traveling at a speed of 41-80km / h, the car window will open by 50% (20cm), and when the car is traveling more than 81km / h the car window will open by 25% (10cm).